A pair of aces - Benedict, Marie; Murray, Victoria Christopher (Reese's book club., 2026)
"A gripping novel about two trailblazing women on opposite sides of the law--a prosecutor and a madam--who team up to bring down notorious gangster Lucky Luciano, from the New York Times bestselling authors of the million-copy bestseller The Personal Librarian. Eunice Carter, assistant district attorney for the City of New York and Manhattan's first Black female prosecutor, has her sights set on the one and only Lucky Luciano, head of New York City's five largest organized crime families. Other prosecutors have tried to bring down Lucky, but they've all focused on the crime syndicate's traditional businesses-bootlegging, gambling, loan sharking, and drug dealing-or tax evasion. No one has thought to approach the mob through its hand in prostitution. Until Eunice. But she can't get Luciano alone. Polly Adler has worked long and hard to build up her high-class brothel business. Her client list is filled with well-known names, both the famous and the infamous, who all know her booze is top-notch, her music first-rate, her food exquisite, and her girls the best. But Lucky has gone too far, putting her girls in danger, and Polly finally sees the chance to end his reign once and for all. Together, Eunice and Polly fashion a case utilizing a network of women. Bridging the enormous divide between them and risking their own lives, they assemble evidence bit by bit, under the nose of the man they're trying to convict. It is this very alliance-of two women from vastly different worlds-that launches the most sensational trial New York City has ever seen"--